2019
DOI: 10.20944/preprints201911.0306.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On-Farm Evaluation of Prescription Map-Based Variable Rate Application of Pesticides in Vineyards

Abstract: Canopy characteristics are crucial for accurately and safely determining the pesticide quantity and volume of water used for spray applications in vineyards. The inevitably high degree of intra-plot variability makes it difficult to develop a global solution for the optimal volume application rate. Here, the design procedure of, and the results obtained from, a variable rate application (VRA) sprayer are presented. Prescription maps were generated after detailed canopy characterization, using a multispectral c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This approach showed how satellite imagery is unusable for crops grown in rows, for crop canopies which do not extend to the whole surface, or where the presence of weeds is significant. Campos et al [ 99 ] designed a procedure for a variable rate application (VRA) sprayer. An unmanned aerial vehicle, equipped with a multispectral camera, was used to generate a photo set for the canopy characterization throughout the entire growing season in four vineyard plots.…”
Section: Unmanned Aerial Systems (Uass) Application In Viticulturamentioning
confidence: 99%
“…This approach showed how satellite imagery is unusable for crops grown in rows, for crop canopies which do not extend to the whole surface, or where the presence of weeds is significant. Campos et al [ 99 ] designed a procedure for a variable rate application (VRA) sprayer. An unmanned aerial vehicle, equipped with a multispectral camera, was used to generate a photo set for the canopy characterization throughout the entire growing season in four vineyard plots.…”
Section: Unmanned Aerial Systems (Uass) Application In Viticulturamentioning
confidence: 99%
“…A low leaf density allows the droplets to pass through the canopy, thus not being deposited on the leaves, what also hinders the target coverage. Similarly, Campos et al (2020) found that higher vegetative volumes increase the deposition of droplets along the canopy.…”
Section: Resultsmentioning
confidence: 87%
“…On average, the electrostatic application results in a 38.0 % higher deposition rate than the hydropneumatic application in the upper third of the plant. Sasaki et al (2013) and Salcedo et al (2020) * Significant at 0.05; ns non-significant at 0.05. Spray technology for deposition of droplets on coffee leaves and fruits observed similar values, but for the entire plant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations